Analisis Penilaian Kinerja, Reward, dan Punishment terhadap Kinerja Pegawai pada Badan Kepegawaian Daerah Provinsi Jawa Timur - Ilham Wahyu Pratama; Gendut Sukarno (Jurnal Ekonomi, 2021)
The success of the company is largely determined by the human resources in it. Therefore, the company must empower all components of its human resources properly, so that they are able to improve their performance by paying attention to performance appraisals, rewards, and punishments to employees. The purpose of this study was to determine the effect of performance appraisal, reward, and punishment on employee performance at the Regional Personnel Agency of East Java Province. This research is a quantitative research that uses a questionnaire as a data collection method. The population used in this study were employees at the Regional Personnel Agency of East Java Province, amounting to 108 people. For the sample who filled out the questionnaire at the Regional Personnel Agency of East Java Province as many as 107 people using probability sampling technique. The data used are primary and secondary data. While the analysis used is Partial Least Square (PLS). The results in this study indicate that 1) performance appraisal has a positive effect on employee performance at the Regional Personnel Agency of East Java Province, 2) reward has a positive effect on employee performance at the Regional Personnel Agency of East Java Province, 3) punishment has not been able to affect employee performance at the Civil Service Agency. East Java Province.